Outlaw rhetoric : figuring vernacular eloquence in Shakespeare's England - Mann, Jenny C. (Jenny Caroline), 1978- (Cornell University Press, 2012)
Using English Renaissance rhetoric manuals in conjunction with the literary texts informed by them, Jenny C. Mann argues that one of the main cultural projects of the English Renaissance, namely its desire to elevate the English language and place it on a level with Latin and Greek, was beset with problems and conflicts from the start.